NANOCRYSTALLINE MECHNICALLY ALLOWED MODIFIING LIGATURES FOR PRODUCTION OF CHROMIUM BRONZE - F. G. Lovshenko; G. F. Lovshenko; I. A. Lozikov (Литьë и металлургия)
Theoretically justified and experimentally confirmed the high efficiency of the technology, based on the reactive mechanical alloying to produce nanocrystalline modifying modifiers and ligatures. Application designed mechanically alloyed modifying ligatures allows to simplify and make cheaper manufacturing process and ensures the formation of dispersion strengthened heat-resistant material with a sub -,/ microcrystalline structure type basis, which results in a significant improvement of the complex of physical and mechanical properties and performance properties of chromium bronze.